Tumor cell apoptosis mediated by the orexins - A. S. Diatlova (SPb RAACI, 2021)
Orexins A and B are neuropeptides synthesized by a population of lateral hypothalamic neurons. Orexin’s physiological function consists mainly in regulating the sleep-wake cycle, eating behavior, and energy homeostasis. Axons of orexin-containing neurons are projected onto many structures of brain and spinal cord, thus providing a variety of their physiological effects. Moreover, the components of the orexinergic system are identified in various peripheral organs and tissues. The effects of orexins are mediated via two receptors (OX1R and OX2R) coupled with G-proteins (GPCRs). The classical signal transmission pathway through orexin receptors in neuronal cells includes an increase of the intracellular calcium as a result of the opening of TRPC membrane channels and IP3 endoplasmic reticulum (ER) channels. In addition to the classic orexin receptors signaling, there is an alternative pathway. Signal transmission through the alternative pathway leads to apoptosis of tumor cells. This pathway is probably due to the structural feature of orexin receptors compared to other GPCRs — the presence of a tyrosine-based immunoreceptor inhibition motif (ITIM). Such motifs are not limited to GPCRs, but are a hallmark of immuno-inhibiting receptors on lymphoid and myeloid cells. ITIM recruits either SHP1 and SHP2 protein tyrosine phosphatases or SHIP1 and SHIP2 inositol phosphatases, to mediate negative signal transduction. A further mechanism of the so-called orexin-induced apoptosis seems to include the p38/MAPK phosphorylation and the cytochrome c releasing from mitochondria, followed by activation of caspases 3 and 7 and cell death. It should be emphasized that this alternative pathway is present only in certain types of tumor cells. This review summarizes the available data on orexin-induced apoptosis of tumor cells from intestines, pancreas, stomach, prostate, endometrium, adrenal glands and glia, and also considers possible mechanisms for its implementation.